Identification of the Long-Term Equilibrium between the UK Capital Market and the Capital Markets of the Visegrad Group - Marek ZINECKER; Michał Bernard PIETRZAK; Tomas MELUZIN; Adam P. BALCERZAK (Communications of International Proceedings, 2020)
The subject of the article concerns the issue of interdependence between capital markets and the problem of identifying the long-term equilibrium between these markets. The phenomenon of interdependence between markets is an element of their functioning, however, the progressive globalization of world economies significantly strengthens the system of mutual connections. The subject matter is important as the last world financial crisis of 2008 has shown that it is possible to shift shock effects from financial markets in one economy to other countries, which results in crisis situations not only in the financial sphere, but also destabilising the real economy. The main goal of the article is to establish a long-term equilibrium between the UK capital market as the main capital market in Europe and the capital markets of the Visegrad Group countries, which can be considered as the markets of local importance. The article presents a research hypothesis stating that there is present the similar long-term development of interdependencies between selected capital markets. The DCC-GARCH model with a conditional t-student distribution was used to measure the interdependence, on the basis of which the conditional correlations for the established pairs of capital markets were determined. The article presents a cointegration analysis for conditional correlations between selected capital markets, and then estimates the parameters of the VECM model were obtained. An equation has been established to define the long-term equilibrium between capital markets and the short-term equation. The obtained results allowed for the verification of the research hypothesis regarding the existence of a long-term path for the course of the interdependence between the capital markets of Great Britain, Poland, the Czech Republic and Hungary.
Keywords: Capital market; cointegration analysis; DCC-GARCH model; conditional variance; conditional correlation.